Investigation of Steric Influences on Hydrogen‐Bonding Motifs in Cyclic Ureas by Using X‐Ray, Neutron, and Computational Methods. Issue 11 (8th August 2013) - McCormick, Laura J.; McDonnell‐Worth, Ciaran; Platts, James A.; Edwards, Alison J.; Turner, David R.
Abstract: A series of urea‐derived heterocycles, 5N‐substituted hexahydro‐1, 3, 5‐triazin‐2‐ones, has been prepared and their structures have been determined for the first time. This family of compounds only differ in their substituent at the 5‐position (which is derived from the corresponding primary amine), that is, methyl (1 ), ethyl (2 ), isopropyl (3 ), tert ‐butyl (4 ), benzyl (5 ), N, N ‐(diethyl)ethylamine (6 ), and 2‐hydroxyethyl (7 ). The common heterocyclic core of these molecules is a cyclic urea, which has the potential to form a hydrogen‐bonding tape motif that consists of self‐associative R_2^2 (8) dimers. The results from X‐ray crystallography and, where possible, Laue neutron crystallography show that the hydrogen‐bonding motifs that are observed and the planarity of the hydrogen bonds appear to depend on the steric hindrance at the α‐carbon atom of the N substituent. With the less‐hindered substituents, methyl and ethyl, the anticipated tape motif is observed. When additional methyl groups are added onto the α‐carbon atom, as in the isopropyl and tert ‐butyl derivatives, a different 2D hydrogen‐bonding motif is observed. Despite the bulkiness of the substituents, the benzyl and N, N ‐(diethyl)ethylamine derivatives have methylene units at the α‐carbon atom and, therefore, display the tape motif. The introduction of a competing hydrogen‐bond donor/acceptor in the 2‐hydroxyethyl derivative disrupts the tape motif, with a hydroxy group interrupting the NH⋅⋅⋅OC interactions. The geometry around the hydrogen‐bearing nitrogen atoms, whether planar or non‐planar, has been confirmed for compounds 2 and 5 by using Laue neutron diffraction and rationalized by using computational methods, thus demonstrating that distortion of O‐C‐N‐H torsion angles occurs to maintain almost‐linear hydrogen‐bonding interactions. Abstract : The incredible bulk : A series of cyclic ureas has been studied to examine the influence of bulky substituents on the hydrogen‐bonding motifs that form and the degree to which the urea group can be distorted to maintain strong intermolecular contacts.